Efficacy and Toxicity in Gardenia Fructus Application: Dual Role Effects Mediated by Gut Microbiota-Derived Biotransformation - Zixin Zhao; Shilin Gong; Chunyue Liu; Jun Wen; Tingting Zhou (Acupuncture and Herbal Medicine, 2026)
Gardeniae Fructus (GF) is a well-known traditional Chinese medicine widely used in clinical prescriptions for its antidepressant, hepatoprotective, and other therapeutic effects. It contains multiple bioactive compounds including iridoid glycosides, crocins, flavonoids and organic acids. However, prolonged use or excessive doses of GF may lead to chronic or acute hepatotoxicity. This dual-edged pharmacological profile has become a major obstacle to its clinical application. Accumulating evidence indicates that the gut microbiota plays a nonnegligible role in the metabolism of traditional Chinese medicines. Notably, the dual effects of GF, both therapeutic and toxic, are closely associated with the microbial biotransformation of its active components, positioning the gut microbiota as a critical determinant of GF's efficacy and safety. Microbial enzymes may enhance the bioavailability and bioactivities of GF-derived ingredients, as well as generate novel metabolites with potential pharmacological activities. Concurrently, GF-induced alterations in bacterial composition may lead to changes in metabolic output, which further influence host physiological responses, thereby modulating the overall effects of GF. In this case, it is essential to incorporate gut microbiota-mediated bioactivities into the comprehensive evaluation of GF pharmacology. This review provides a comprehensive summary of the main bioactive compounds of GF and their biotransformation by the gut microbiota, as well as claiming the dual role effects of GF in the presence or absence of gut microbiota influences. Moreover, we discuss the potential of intestinal bacterial modulation as a strategy for balancing the efficacy and safety of GF. This review offers a thorough synthesis of the dual pharmacological actions of GF, while placing particular emphasis on the gut microbiota as a critical mediator of its divergent effects. We also offer new perspectives on the clinical potential of gut microbiota-targeted interventions to balance the dual effects of GF. The bidirectional crosstalk between gut microbiota and GF significantly influences the efficiency and toxicity of drugs. Ecological management strategies may benefit the personalized treatment paradigm of GF considering the personal gut microbiota variabilities. Graphical Abstract: https://links.lww.com/AHM/A240